2017
DOI: 10.1038/s41540-017-0003-6
|View full text |Cite
|
Sign up to set email alerts
|

Neighbours of cancer-related proteins have key influence on pathogenesis and could increase the drug target space for anticancer therapies

Abstract: Even targeted chemotherapies against solid cancers show a moderate success increasing the need to novel targeting strategies. To address this problem, we designed a systems-level approach investigating the neighbourhood of mutated or differentially expressed cancer-related proteins in four major solid cancers (colon, breast, liver and lung). Using signalling and protein–protein interaction network resources integrated with mutational and expression datasets, we analysed the properties of the direct and indirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 77 publications
0
28
0
Order By: Relevance
“…Beside using interaction networks to identify disease-related modules and key proteins, it has also been used for finding novel pathogenetic players among the interactor partners of already known, key pathogenic genes by "guilt by association". We previously used this approach to identify potential drug repurposing targets in cancer 28 . In the current study we integrated all these three network reconstruction and analysis methodologies to understand the pathogenesis of complex diseases, such as UC better.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beside using interaction networks to identify disease-related modules and key proteins, it has also been used for finding novel pathogenetic players among the interactor partners of already known, key pathogenic genes by "guilt by association". We previously used this approach to identify potential drug repurposing targets in cancer 28 . In the current study we integrated all these three network reconstruction and analysis methodologies to understand the pathogenesis of complex diseases, such as UC better.…”
Section: Discussionmentioning
confidence: 99%
“…The network footprint of each patient contained the proteins encoded by the SNP-affected genes and the interactors of these proteins, i.e. their first neighbour proteins 28 . Unsupervised hierarchical clustering using different linkage algorithms and multidimensional scaling of the network footprints of 377 patients stratified the patients into the same four distinct clusters (Figures 3a and 3b).…”
Section: Identification Of Patient-specific Clusters Based On the Netmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Disrupting a PPI by directly binding to the interfacial surface (2) Disrupting a PPI by allosteric interference (3) Allosterically increasing the binding affinity to the protein partner (4) Stabalize PPI by direct binding to the interacting surface Recent studies ((Modos et al, 2017)) show that neighbors of proteins implicated in cancer have a high degree of centrality in biological networks. They have clearly shown that first neighbor of cancer-related proteins have high local and global centrality in the network.…”
Section: Discussionmentioning
confidence: 99%
“…In the presented analysis, the nodes of the interaction networks represent genes/molecules of interest from the transcriptomics data and the edges represent regulatory connections (molecular interactions) between the nodes inferred from databases. Studying regulatory interactions using interaction networks has been proved useful to uncover how cells respond to changing environments at a transcriptional level, to prioritise drug targets and to investigate the downstream effects of gene mutations and knockouts (32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%